Palaeoendemic plants provide evidence for persistence of open, well‐watered vegetation since the Cretaceous. Issue 2 (10th November 2015) - Jordan, Gregory J.; Harrison, Peter A.; Worth, James R. P.; Williamson, Grant J.; Kirkpatrick, James B.
Abstract: Aim: Palaeoendemics are clades that are ancient but geographically restricted, often because they have been selected against in other areas. Ecological similarities among palaeoendemics may be indicators of ancient environments. We determine the environmental ranges of the remarkable palaeoendemic plants of Tasmania to deduce whether they indicate the long‐term persistence of particular environmental conditions. Location: Tasmania, Australia, a global centre of plant palaeoendemism, containing some of the world's most relictual plant lineages. Methods: Palaeoendemic clades in Tasmania were identified using a scoring system of clade age divided by the square root of the number of 10 km × 10 km grid cells occupied globally. Total palaeoendemism scores for 1199 30″ grid cells were calculated by summing scores for individual clades, and modelled against climate, topography, geology and vegetation type using Random Forest models. Palaeoendemic and non‐palaeoendemic species richness in climate space was measured. The global distribution of climates favoured by palaeoendemics was assessed. Results: Twenty‐nine phylogenetically and ecologically diverse palaeoendemic clades (51 species) were identified. High levels of palaeoendemism occurred widely in western Tasmania, but the highest scoring areas were at or slightly above the tree line in relatively undisturbed vegetation. Palaeoendemism scores were strongly predicted by constantly moist climates lacking extreme temperatures, and by open vegetation types with rare or no fire. The palaeoendemics occupied a climate space that is globally rare and very different from that of non‐palaeoendemics. Main conclusions: These patterns suggest the persistence since the Cretaceous of open vegetation in constantly moist areas with equable temperatures and few or no fires. This conclusion is consistent with an increasing body of fossil and phylogenetic evidence for the antiquity of open vegetation. The methods here produce quantitative values of palaeoendemism that can be compared among regions.